Fusobacterium necrophorum associated with pelvic infections: A case series and literature review - Manasa Brown; Sabrina Imam; Jade Pagkas-Bather (IDCases)
Fusobacterium necrophorum is a gram-negative anaerobic bacillus most commonly implicated in oropharyngeal infections and their subsequent complications, including septic thrombophlebitis of the internal jugular vein, or Lemierre syndrome. However, limited case reports document evidence of pelvic infections associated with Fusobacterium as well, such as pelvic peritonitis and pelvic septic vein thrombophlebitis. In this case series, we discuss two occurrences of Fusobacterium necrophorum bacteremia from a presumed gynecologic source and present a literature review of other reported cases of Fusobacterium associated with female pelvic etiology. While current data describe a greater prevalence of Fusobacterium infections overall in men compared to women, more information is needed regarding the clinical significance of female-specific risk factors that may predispose to this disease.